A pragmatic approach to vasculitis in the gastrointestinal tract. Issue 6 (24th January 2017) - Chetty, Runjan; Serra, Stefano
Abstract : Although vasculitis involving the gastrointestinal tract (GIT) is an uncommon occurrence, occasionally vasculitis can present as haemorrhagic infarction or ischaemia for which a length of bowel is removed. Invariably, the appropriate clinical history is not forthcoming, or vasculitis is not clinically suspected. The purpose of this overview is to provide the practising gastrointestinal (GI) pathologist with a framework to recognise and diagnose vasculitides within the GIT. The classification may be approached by aetiological agent or size of vessel involved; an international consensus group now favours the latter approach. The symptoms that systemic and/or localised vasculitis may cause in the GIT are protean and non-specific. As a result, pathologists examining resection specimens for unexplained haemorrhagic infarction or ischaemia should be aware that vasculitis may be a potential cause. Several well-known systemic vasculitides such as polyarteritis nodosa, microscopic polyangiitis, eosinophilic granulomatosis with polyangiitis or Churg-Strauss syndrome and granulomatosis with polyangiitis or Wegener's granulomatosis can occur in the GIT. The latter three constitute the antineutrophil cytoplasmic antibody-positive vasculitides. In addition, the so-called solitary organ vasculitis (SOV) can occur in the GIT as the harbinger of later onset systemic vasculitis, and be the cause of the GIT symptoms. In addition, SOV can occur incidentally and coexist with GIT disease such as gallstones or polyps, and there may be no manifestations of systemic vasculitis for years, or not at all.